Pengaruh Karakter Kewirausahaan Terhadap Inovasi Pengolahan Hasil Perikanan Pada Anggota Kelompok Usaha Bersama (KUB) di Kecamatan Pemangkat - Harmoko Harmoko; Winda Apriani (Eqien - Jurnal Ekonomi dan Bisnis, 2023)
The business of fishery processing becomes an economic booster in Pemangkat coastal area. It was due in part to individual characteristics integrated with the business group, which is certainly having an entrepreneurial spirit. Thus, the entrepreneurship characteristics in joint ventures need attention. The present research aims to determine the effect of innovation entrepreneurship characteristics on joint venture members in Pemangkat districts. The research was obtained on 6 business groups, consisting of 9 respondents per group using a random method. Thus, the total samples were 54 respondents. The research used linear regression analysis. The dependent variable was the fishery processing innovation, whereas the independent variables were motivation, the confidence in being successful, and the attitude toward professions. Results showed that the entrepreneurship characteristics affected motivation and professional attitude in fishery processing. The implication of the result was the fishery processing community had encouragement to be confident in their profession given in training, guidance, or workshop.